Analisis Perbandingan Pengolahan Citra Asli Dan Hasil Croping Untuk Identifikasi Telur - Shoffan Saifullah; Sunardi -; Anton Yudhana (Maranatha University Press, 2016)
Thermal imaging camera and smartphone camera are the impacts of rapid technological development. This research uses two tools to take pictures of chicken eggs. Images of chicken eggs from the two tools are used to identify of size, determination of object and analysis of image cropping from the samples have used. Process analysis using Matlab prototype for image processing began with histogram, converting the image to grayscale or black white, then the process is carried region props, centroid and the bounding box and labeling. Process analysis using Matlab prototype for image processing began with histogram, converting the image to grayscale or black white, then the process is carried region props, centroid, bounding box and labeling. The process of identification egg objects with region props and labeling can be successfully performed with a 100 % success rate. Images of each sample were conducted to provide data that the cropping process gives the area to the smaller / less identifiable objects provide little value and uniform for any number of the same object. The identification process on the image of the chicken egg thermal cameras and smartphone cameras give equal areas. However, each data cropping of the process is done, the image from the thermal cameras and smartphone cameras give different values. So the cropping process provides the difference in the identification process of chicken eggs. The difference of the image processing of thermal cameras and smartphone cameras lies in the preprocessing of images of thermal cameras needed to complement and process images from the camera smartphone needs to process with the opening before to do the region props and labeling process getting the object is identified.